Limonium korakonisicum (Plumbaginaceae), a new species from Zakynthos Island (Ionian Islands, Greece) - Valli, Anna-Thalassini; Artelari, Rea (Phytotaxa, 2015)
Limonium korakonisicum (Plumbaginaceae), a new species from Zakynthos Island (Ionian Islands, Greece), is described and illustrated from the only known population (locality Korakonisi) located in the southwestern coast of the island. The hexaploid chromosome number (2n=6x=51), the karyotype and the self-incompatible pollen-stigma combination A (‘A’pollen and ‘Cob’ stigma), support that L. korakonisicum is an apomictic taxon originated through hybridization. This new taxon is related to the polyploid apomictic Limonium species which are prevalent in the Aegean area and especially to the recently described Cytherian endemic L. spreitzenhoferi Erben & Brullo. The morphological differences of L. korakonisicum from L. spreitzenhoferi as well as from the sexual diploid endemic L. phitosianum, which coexists at the same locality, are discussed. Data on the ecology and conservation status of the new species are also given.